2015
DOI: 10.7322/jhgd.106010
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Food Consumption as Predictor of Cardiovascular Risk and Waist Circumference Increase in Teenagers

Abstract: INTRODUCTIONThe eating habits of young people have changed significantly over the last few decades. Studies show that teenagers tend to have less than desirable intake of fruits, vegetables, dairy products and wholegrain products, with a higher intake of soft drinks, sweets and fast food. As a result, most teenagers fall short of achieving optimal nutrient intake for healthy development 1,2 .Obesity, hypertension and dyslipidaemia are closely associated with cardiovascular disease 3 and the prevalence of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Thus, the increase in caloric intake volume, coupled with the sharp decline in daily physical activity levels among teens [23][24][25] , and even further among overweight subjects 26 , corresponded to important determinants for increasing adiposity and body weight. However, the association between abdominal obesity and inadequate dietary habits has not yet been fully verified in the literature 27 . The association between abdominal obesity and lower levels of physical activity was not observed in this study, which was also not observed by Salvador et al 8 One possible explanation is due to the fact that subjects suffering from abdominal obesity can engage in physical activity in an attempt to reduce adiposity, which thus results in a reverse causality phenomenon and inhibits possible inferences.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the increase in caloric intake volume, coupled with the sharp decline in daily physical activity levels among teens [23][24][25] , and even further among overweight subjects 26 , corresponded to important determinants for increasing adiposity and body weight. However, the association between abdominal obesity and inadequate dietary habits has not yet been fully verified in the literature 27 . The association between abdominal obesity and lower levels of physical activity was not observed in this study, which was also not observed by Salvador et al 8 One possible explanation is due to the fact that subjects suffering from abdominal obesity can engage in physical activity in an attempt to reduce adiposity, which thus results in a reverse causality phenomenon and inhibits possible inferences.…”
Section: Discussionmentioning
confidence: 99%